2012
DOI: 10.1088/0022-3727/45/13/135202
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of pulsed RF corona discharges in high-pressure air

Abstract: An approach to description of pulsed RF corona discharges in high-pressure air is developed, based on the model of a filamentary discharge sustained by an electromagnetic wave guided along the plasma filament. Results of numerical simulation of spatial-temporal discharge dynamics at the quasi-stationary stage are obtained for various values of gas pressure and wave frequency. Experimental data on the discharge length versus the power absorbed by the discharge are presented. Their comparison with simulation res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…With the rapid development of pulsed power technology, a pulsed power supply with a fast rise time and a high overvoltage has been used to drive high-voltage discharges due to its high peak power [24][25][26][27][28][29][30][31]. Burlica and Locke obtained pulsed gliding discharges using a bipolar millisecond pulsed power supply; their experimental results showed that the energy yield for the destruction of an organic blue dye in a pulsed gliding discharge was 150 times higher than that in an ac gliding discharge [32].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of pulsed power technology, a pulsed power supply with a fast rise time and a high overvoltage has been used to drive high-voltage discharges due to its high peak power [24][25][26][27][28][29][30][31]. Burlica and Locke obtained pulsed gliding discharges using a bipolar millisecond pulsed power supply; their experimental results showed that the energy yield for the destruction of an organic blue dye in a pulsed gliding discharge was 150 times higher than that in an ac gliding discharge [32].…”
Section: Introductionmentioning
confidence: 99%
“…The RF energy can be efficiently delivered to the discharge tips only if the system is optimally tuned, including treating the cylinder charge as a part of the electric circuit-a virtual capacitor. According to the publicized results, 51,[81][82][83][84][85][86][87][88][89][90][91][92][93] to date, the leading contenders for RF corona ignition prototyping includes the advanced corona ignition system (ACIS) by Federal Mogul and the Ecoflash corona ignition system by BorgWarner. One of the challenges of RF corona ignition is ensuring the inception of corona discharge while avoiding arc touchdown, especially in high-density conditions when a higher voltage is demanded.…”
Section: Rf Corona Ignitionmentioning
confidence: 99%
“…In addition to the difficulty to model the non-thermal plasma effect, for RF corona ignition, it is also of great challenge to predict the spatial distribution of the plasma branches, even though the energy and propagate distance of the plasma could be modelled. 91 Because of the promising potentials, advanced ignition technologies are deemed as a key enabler for high efficiency in future combustion engines. Significant advances in scientific understandings and engineering technologies are expected in order to tackle the associated challenges.…”
Section: Challenge and Outlookmentioning
confidence: 99%
See 1 more Smart Citation